Peran Agama dalam Mereduksi Penyalahgunaan Narkoba (Studi Kasus Warga Binaan Wanita di Lembaga Pemasyarakatan Kelas II B Padangsidimpuan) - Fikri, M.Ag, Dr. Sholeh; Andriani, Wildah (Institut Agama Islam Negeri Padangsidimpuan, 2020)
AbstractThe purpose of this research in this thesis is to the find out the implementation of Islamic guidance in class II B penitentiary in Padangsidimpuan, to know the material provided in Islamic guidance in class II B penitentiary in Padangsidimpuan and to know the method used by the supervisor to provide Islamic guidance to fostered citizens in Class II Correctional institutions in Class II Correctional Institutions B Padangsidimpuan. The type of research used is descriptive qualitative research and tends to use analysis with an inductive approach. The approach used is a descriptive approach which aims to describe the object as it is. The primary data source is 3 people, namely 1 head of the security and order section and 2 ministry of religion officuers while the secondary data source is 13 people, 10 dealers and 3 drug users. Data techniques used were observation, interviews and documentation. While data processing and analysis techniques, namely data reduction, descriptive data, drawing conclusions, checking techniques and the validity of the data used are triangulation of data sources. Based on the results of this study it can be concluded that Islamic guidance in reducing drug abuse in Class II B Padangsidimpuan. The implementation of Islamic guidance in reducing drug abuse in the from of lectures, reading the Qur’an, Dhikr and Du’a, guidance of personality and independence. Then the material provided in Islamic guidance is Aqeedah, Sharia and Morals. While the method of Islamic guidance, namely al-hikmah, want’izhoh Hasanah, Mujadalah. So that some women-assisted residents have very noticeable changes in themselves, so that they become a better person and a lot of creativity can be done to open business opportunities after being released later from Class II B Penitentiary in Padangsidimpuan.